Intestinal anti-inflammatory activity of Ground Cherry (Physalis angulata L.) standardized CO2 phytopharmaceutical preparation - Almeida, Luiz Domingues [UNESP]; Quaglio, Ana Elisa Valencise [UNESP]; De Almeida Costa, Celso Acácio Rodrigues [UNESP]; Di Stasi, Luiz Claudio [UNESP] (Baishideng Publishing Group, 2017)
AIM To investigate the effects of Ground Cherry (Physalis angulata L.) standardized supercritical CO2 extract in trinitrobenzenesulphonic acid (TNBS) model of rat intestinal inflammation. METHODS The animals were divided into groups that received vehicle or P. angulata extract (PACO2) orally at the doses 25, 50 and 100 mg/kg daily by 5 d before TNBS damage. Protective effects of PACO2 were assessed by macroscopic analysis, biochemical determinations of the levels of myeloperoxidase (MPO), alkaline phosphatase (ALP), glutathione and cytokines (such as INF-γ, IL-1β, IL-6, IL-10 and TNF-α), gene expression evaluation (including Hsp70, heparanase, NF-κB, mitogenactivated protein kinases (Mapk) 1, 3, 6 and 9, and the mucins genes Muc 1, 2, 3 and 4) and histopathological studies using optical, and electronic (transmission and scanning) microscopy. RESULTS PACO2 extract promoted a significant reduction in MPO and ALP activities, reducing oxidative stress and neutrophil infiltration. These effects were accompanied by significant reduction of colonic levels of IFN-γ and IL-6 and down-regulation of heparanase, Hsp70, Mapk3, Mapk9, Muc1 and Muc2 genes expression when compared with TNBS-control animals. In addition, protective effects were also evidenced by reduced neutrophil infiltration, recovery of cell architecture and replacement of mucin by histopathological and ultrastructural analysis. CONCLUSION Physalis angulata supercritical CO2 extract is an intestinal anti-inflammatory product that modulates oxidative stress, immune response and expression of inflammatory mediators, with potentially utility for treating inflammatory bowel disease.
Keywords: Inflammatory bowel disease; Intestinal disease; Physalis angulata L. trinitrobenzenesulphonic acid